Aviation fuel problems at high altitudes and high aircraft speeds - Goodger, E. M. (College of Aeronautics, 1959)
Much useful data has appeared over recent years concerning the problems incurred by continued increases in operational altitudes and aircraft speeds. This report is an attempt to correlate a representative amount of these data, and to present them in a form suitable both for general information and for project design reference. Frequent references are made to the literature as guides to additional information. Some of the work has formed the basis of research activities at Cranfield.